The aesthetics of Japanese fascism - Tansman, Alan, 1960- (Studies of the Weatherhead East Asian Institute, Columbia University., 2009)
In this wide-ranging study of Japanese cultural expression, Alan Tansman reveals how a particular, often seemingly innocent aesthetic sensibility, present in novels, essays, popular songs, film, and political writings, helped create an "aesthetic of fascism" in the years leading up to World War II. Evoking beautiful moments of violence, both real and imagined, these works did not lead to fascism in any instrumental sense. Yet, Tansman suggests, they expressed and inspired spiritual longings quenchable only through acts in the real world. Tansman traces this lineage of aesthetic fascism from its beginnings in the 1920s through its flowering in the 1930s to its afterlife in postwar Japan